THE LINGUODIDACTIC APPROACH TO COMPARATIVES IN LANGUAGE (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This comprehensive article meticulously dissects the linguodidactic approach applied to teaching and understanding comparatives within language learning contexts. It systematically explores the multifaceted components of the approach, ranging from linguistic analysis to the integration of diverse teaching methodologies. Emphasizing the significance of context-based learning, the article elucidates the practical application of comparative structures in real-life scenarios, bolstered by interactive exercises and error correction strategies. Importantly, it highlights the cultural relevance intertwined with comparative language use, fostering a deeper appreciation for linguistic nuances. The article’s holistic approach, encompassing multilingual comparisons, advanced structures, and adaptive teaching strategies, underscores its relevance for diverse learner profiles. It also underscores the role of technology, continual reinforcement, and ongoing professional development for educators, reflecting a forward-thinking perspective on language instruction. Overall, this article serves as an invaluable resource for educators and learners alike, offering a comprehensive guide to mastering comparatives while navigating the intricacies of language acquisition.